2008
DOI: 10.2514/1.33073
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production from Surface Recombination of Oxygen and Nitrogen Atoms

Abstract: Experimental results are presented that support the surface-catalyzed production of nitric oxide from the recombination of oxygen and nitrogen atoms on quartz. The experiments employ two-photon laser-induced fluorescence detection of atomic oxygen and atomic nitrogen to characterize changes in gas-phase atom concentrations as the ratio of O to N atoms is varied at the opening of a diffusion-tube side-arm reactor. The measurements verify a correlation between decreased O-atom loss and enhanced N-atom loss in N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…We have recently strengthened the experimental evidence provided by Copeland et al [3] by adding sequential N-and O-atom LIF diagnostics and simultaneous concentration measurements at four different sidearm locations [4]. These measurements reproduced the findings of Copeland et al [3] and confirmed their prediction of decreased O-atom loss in O=N mixtures.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…We have recently strengthened the experimental evidence provided by Copeland et al [3] by adding sequential N-and O-atom LIF diagnostics and simultaneous concentration measurements at four different sidearm locations [4]. These measurements reproduced the findings of Copeland et al [3] and confirmed their prediction of decreased O-atom loss in O=N mixtures.…”
supporting
confidence: 78%
“…In our previous room-temperature experiments, reasonable agreement was found between measured and simulated O-atom and N-atom profiles along the sidearm tube by setting O N 1 10 5 and specifying f O;O 2 f N;N 2 0:5 [4]. The loss probability of O and N atoms by surface recombination on quartz increases with temperature, although the reported magnitude and functional dependence of this effect varies greatly between researchers [6][7][8][9][10].…”
Section: B Simulation Resultsmentioning
confidence: 60%
See 3 more Smart Citations